Voting Behavior in India: Comprehensive Overview : भारत में मतदान व्यवहार: समग्र अवलोकन - Rathore, Shipra; Meena, Chetram (RESEARCH HUB International Multidisciplinary Research Journal, 2024)
There is a misconception prevalent in certain political circles that the people of India cannot exercise their right to vote with propriety or discretion, because they are victims of illiteracy, poverty, caste animosity, religious fanaticism etc. But the voting behavior of the Indian people from the first general election till now confirms the fact that the above misconception is only of those people who do not understand the mind and brain of the Indian people, who do not understand the character and thinking of the voters of India. Till now, the Indian voters have shown discretion and efficiency in their voting, barring some exceptions, they have displayed discipline and have understood the value of voting rights. However, it is also true that in view of the diversity of India, its various factors have had a wide impact on the mindset and voting behavior of the voters. We should also be assured of the fact that their strong will is to maintain democracy. Therefore, we can say that the voting behavior of Indians is the pillar of democracy. Abstract in Hindi Language: कतिपय राजनीतिक क्षेत्रों में ऐसी भ्रामक धारणा व्याप्त है कि भारत की जनता अपने मताधिकार का प्रयोग औचित्य अथवा विवेक के साथ नहीं कर सकती, क्योंकि वह अशिक्षा, गरीबी, जातिगत द्वैष, धर्मान्धता आदि की शिकार है, लेकिन प्रथम आम चुनाव से लेकर अब तक भारतीय जनता का जो मतदान व्यवहार रहा है उससे इसी तथ्य की पुष्टि होती है कि उपर्युक्त भ्रामक मत केवल उन्हीं लोगों का है जो भारतीय जनता के मन मस्तिष्क को नहीं समझते, जिन्हें भारत के मतदाताओं के चरित्र एवं चिन्तन का बोध नहीं है। अभी तक भारतीय मतदाताओं ने अपने मतदान में जिस विवेक और कुशलता का परिचय दिया है, कुछ अपवादों को छोड़कर अनुशासनप्रियता प्रदर्शित की है और मताधिकार की कीमत समझी है। हालांकि यह भी सही है कि भारत की विविधता को देखते हुए उसके विभिन्न कारकों का व्यापक प्रभाव मतदाताओं की मानसिकता तथा मतदान व्यवहार पर पड़ा है। हमें इस तथ्य के प्रति भी आश्वस्त होना चाहिए कि उनकी दृढ़ इच्छा लोकतन्त्र को कायम रखने में है। अतः कह सकते हैं, भारतीयों का मतदान व्यवहार, लोकतन्त्र के लिए आधार स्तम्भ है। Keywords: भारत, चुनाव, राजनीतिक दल, मतदान व्यवहार, लोकतंत्र, मतदाता